Comparison of the efficacy of Ivabradine and Nebivolol as Mono Therapy in the Treatment of Stable Angina Pectoris Patients with Mild Left Ventricular Dysfunction - Hoque, Harisul; Ahmed, Khurshed; Mandal, MRM; Kabir, Faisal Ibn; Salam, Md Abdus; Fatema, Nilufar (University Heart Journal, 2019)
This prospective study aimed to investigate the efficacy of ivabradine and nebivolol in treatment of stable angina pectoris (SAP) patients with mild left ventricular dysfunction. Heart rate decreased (78±6) to (65±5) in Group: A and ( 77± 7) to (70 ± 5) in Group: B. There was no change in Blood pressure reduction in Group:A but significant BP reduction in Nebivolol group. Chest pain was reduced by Ivabradine but in Group : B, chest pain decreased in long term after 6 weeks time. After 6 months’ treatment LVEF for the 15 patients of nebivolol group (50%; Group: A) improved by (48 ± 6.5) to (51 ± 3.2), (p>0.05) and for the 15 patients of Ivabradine group (50%; Group: B) (47 ± 5.4) to (51 ± 2.3), (p>0.05). Ivabradine can be considered as first choice in patient with tachycardia induced angina as this agent for reducing heart rate as well as chest pain. The hypertensive patient with tachycardia may be treated by Nebivolol. Among patients in which effective treatment could not be achieved at maximum nebivolol doses, more effective results were obtained in this study with Ivabradine. University Heart Journal Vol. 15, No. 1, Jan 2019; 8-11